England's safety: or the two unanimous votes of the last good Parliament concerning the Duke of York being a papist with their address to His Majesty to be revenged on the papists in case His Majesty come by a violent death. Published for the information of all true Protestants, that they may not be afraid, nor ashamed, openly in Parliament to act and oppose any popish successor and his adherents from inheriting the crown of England, in case His Majestie's life (which God forbid) be taken from Him (Early English Books Online / EEBO, 1679)
eebo-0018